2016
DOI: 10.1111/dom.12715
|View full text |Cite
|
Sign up to set email alerts
|

The role of hepatocyte nuclear factor 1β in disease and development

Abstract: Heterozygous mutations in the gene that encodes the transcription factor hepatocyte nuclear factor 1β (HNF1B) result in a multi-system disorder. HNF1B was initially discovered as a monogenic diabetes gene; however, renal cysts are the most frequently detected feature. Other clinical features include pancreatic hypoplasia and exocrine insufficiency, genital tract malformations, abnormal liver function, cholestasis and early-onset gout. Heterozygous mutations and complete gene deletions in HNF1B each account for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
60
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(60 citation statements)
references
References 65 publications
0
60
0
Order By: Relevance
“…These TFs were also part of the hepatocellular carcinoma CRC we predicted for hepatocellular carcinoma from gene essentiality data ( Figure 2B). In addition, our predicted CRC contained additional TFs that have previously been described (El-Khairi and Vallier, 2016;Nguyen et al, 2014) to play important roles during liver development, such as HNF1B (LD-score = 3.79, FDR = 8.66x10 -7 ) or LIN28B (LD-score = 2.29, FDR = 9.06x10 -6 ). As expected, public transcription factor databases (ENCODE Project Consortium, 2004;Lachmann et al, 2010;Matys et al, 2003;Rouillard et al, 2016;Xu et al, 2013) report a large number of TF-target gene relationships (i.e.…”
Section: Clustering Of Cancer Lineages By Ld-scores Revealed Groups Omentioning
confidence: 81%
“…These TFs were also part of the hepatocellular carcinoma CRC we predicted for hepatocellular carcinoma from gene essentiality data ( Figure 2B). In addition, our predicted CRC contained additional TFs that have previously been described (El-Khairi and Vallier, 2016;Nguyen et al, 2014) to play important roles during liver development, such as HNF1B (LD-score = 3.79, FDR = 8.66x10 -7 ) or LIN28B (LD-score = 2.29, FDR = 9.06x10 -6 ). As expected, public transcription factor databases (ENCODE Project Consortium, 2004;Lachmann et al, 2010;Matys et al, 2003;Rouillard et al, 2016;Xu et al, 2013) report a large number of TF-target gene relationships (i.e.…”
Section: Clustering Of Cancer Lineages By Ld-scores Revealed Groups Omentioning
confidence: 81%
“…HNF1B gene played the important role in the primary pathophysiology of diabetes. It was involved in the loss of neurogenin-3 (Ngn3)-positive endocrine progenitor cells, pancreatic atrophy, and a reduced insulin sensitivity to endogenous glucose production leading to the reduction of insulin secretion [32]. Previous studies have reported that genetic variations in HNF1B were associated with the susceptibility of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Early-onset DM cases with renal abnormalities strongly suggest a mutation in the HNF1B gene. Moreover, the pathophysiology of DM in patients with HNF1B mutations is beta-cell dysfunction and reduced insulin secretion as well as reduced insulin sensitivity to endogenous glucose production ( 6 ). The majority of MODY5 patients require early treatment with insulin since they respond poorly to sulphonylureas.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations predominantly cluster in the first four exons, which encode dimerisation and DNA-binding domains. Most of them can explain a transcriptional impairment of the HNF1B protein ( 6 ). Here, sequencing of coding exons and intron–exon boundaries of the candidate genes allowed us to detect a mutation in an intron.…”
Section: Discussionmentioning
confidence: 99%